Research Progress on the Functions and Mechanism of circRNA in Cisplatin Resistance in Tumors - Mu, Qingchun; Lv, Yue; Luo, Chunmei; Liu, Xiaojing; Huang, Chunming; Xiu, Youcheng; Tang, Longguang (Frontiers in Pharmacology, 2021)
Cisplatin is a common chemotherapeutic drug that has been used to treat of numerous tumors, including testicular, lung, bladder, ovarian, liver and head and neck cancers. Although clinical chemotherapy based on cisplatin has shown a remarkable therapeutic effect, the resistance to cisplatin becomes increasingly obvious as a patient uses it for a prolonged period. It not only affects the prognosis of these tumors, but also causes the recurrence of cancer and decreases the overall survival rate. The development of cisplatin resistance involves several mechanisms, including DNA damage repair, ATP-binding cassette (ABC) transporter, autophagy, cancer stem cells (CSCs), epithelial–mesenchymal transition (EMT), and other related signaling pathways. Interestingly, these mechanisms have been found to be influenced by circular RNAs (circRNAs) to regulate tumor proliferation, invasion, chemosensitivity, and other biological behaviors in the tumor microenvironment (TME). In recent years, circRNAs in cisplatin resistance in tumors, especially lung cancer and gastric cancer, have gradually drawn peoples’ attention. This review summarizes recent studies on the functions and mechanisms of circRNAs in cisplatin resistance. We emphasize that circRNA can be used as a promising target gene to reverse drug resistance and improve therapeutic efficacy.